2013
DOI: 10.3389/fnins.2013.00175
|View full text |Cite
|
Sign up to set email alerts
|

Heads for learning, tails for memory: reward, reinforcement and a role of dopamine in determining behavioral relevance across multiple timescales

Abstract: Dopamine has long been tightly associated with aspects of reinforcement learning and motivation in simple situations where there are a limited number of stimuli to guide behavior and constrained range of outcomes. In naturalistic situations, however, there are many potential cues and foraging strategies that could be adopted, and it is critical that animals determine what might be behaviorally relevant in such complex environments. This requires not only detecting discrepancies with what they have recently exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 149 publications
(182 reference statements)
0
21
0
Order By: Relevance
“…In general, the differences in the connection patterns provided by the three types of connections roughly supported the concept that the two NAc subregions have different, or even antagonistic, functions [Baudonnat et al, ]. However, these functions of the two subregions must be interrelated and complementary with each other, as indicated by their anatomical and functional interconnections, including direct and indirect connections via multiple circuits.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In general, the differences in the connection patterns provided by the three types of connections roughly supported the concept that the two NAc subregions have different, or even antagonistic, functions [Baudonnat et al, ]. However, these functions of the two subregions must be interrelated and complementary with each other, as indicated by their anatomical and functional interconnections, including direct and indirect connections via multiple circuits.…”
Section: Discussionmentioning
confidence: 77%
“…The cortical and limbic inputs impinge on and may integrate into the NAc [French and Totterdell, 2003] for the regulation of DA from the MidB [Lodge and Grace, 2006]. DA has been reported to play different roles in the NAc shell and core, involving complementary or even antagonistic functions in some circumstances [Baudonnat et al, 2013]. On the basis of its primary origin from the VTA, the shell was hypothesized to be functionally associated with the mesolimbic dopamine system and to play a critical role in biasing decision-making when a reward is uncertain [Dreyer, 2010;Stopper and Floresco, 2011].…”
Section: Midbmentioning
confidence: 99%
“…Indeed, selective inhibition of MAO-B does not cause significant changes in central nervous system steadystate levels of 5-HT (Green and Youdim, 1975;Twist et al, 1991;Waldmeier, 1987). In addition, several studies have reported that striatal DA may play a key role in motivated behavior and has a direct impact on memory formation in the hippocampus, suggesting hippocampal-striatal DA network interaction that affected learning and memory capabilities [see reviews, (Shohamy and Adcock, 2010;Baudonnat et al, 2013)]. …”
Section: Discussionmentioning
confidence: 99%
“…Dopamine neurons project extensively to striatal and cortical regions where they mediate a diverse array of functions, including reward-related learning, drug-related synaptic plasticity, working memory, and motivation [1][2][3][4][5][6]. Dopamine neurons respond with brief and phasic bursts of action potentials to salient events, such as reward-predictive stimuli and unexpected reward delivery [7,8], and these bursts cause phasic dopamine release in terminal regions, including the prefrontal cortex (PFC) and the nucleus accumbens (NAc) [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%